Characterization of Mouse Thrombin-activatable Fibrinolysis Inhibitor - Marx, Pauline F.; Wagenaar, Gerry T. M.; Reijerkerk, Arie; Tiekstra, Margriet J.; van Rossum, Agnes G. S. H.; Gebbink, Martijn F. B. G.; Meijers, Joost C. M. (Thrombosis and Haemostasis, 2000)
Based on in vitro studies, thrombin-activatable fibrinolysis inhibitor (TAFI) has been hypothesized as a link between coagulation and fibrinolysis, but the physiological role of TAFI in vivo has not yet been established. To anticipate on the availability of genetically modified mouse models, we studied the endogenous expression of TAFI in mice. Functional TAFI was found in mouse plasma. TAFI mRNA was only detectable in the liver, showing a hepatocyte-specific expression with a pericentral lobular distribution pattern. The murine TAFI cDNA was cloned and sequenced. The deduced amino acid sequence revealed that murine TAFI is highly identical to human TAFI. The murine cDNA was stably expressed and the activated recombinant protein was functionally active; it converted the substrate hippuryl-arginine, and prolonged the clot lysis time of TAFI depleted plasma. We conclude that mice have functional TAFI in plasma, which is highly similar to human TAFI. Therefore, genetically modified mice may provide useful models to study the role of TAFI in vivo.Abbreviations: TAFI, thrombin-activatable fibrinolysis inhibitor; CPI, carboxypeptidase inhibitor from potato tubers; CPN, carboxypeptidase N; t-PA, tissue-type plasminogen activator; PPACK, H-D-Phe-Pro-Arg-chloromethylketone.
Keywords: Coagulation; fibrinolysis; thrombin-activatable fibrinolysis inhibitor